Enabling and Limiting factors in eXtreme Programming (XP) with Evaluation Framework - Kunwar, Sundar (SCITECH Nepal, 2019)
As agile software development methodologies are used in many domains and come with different shapes and sizes, it is one of the complex human endeavors. Extreme Programming (XP) is one of the well-known agile software development methodologies and is driven by a set of values including simplicity, communication, feedback and courage, but lacks the mechanism to measure these values demanding the evaluation framework to make it measurable and attainable. The main aim of this study is to build the software process improvement model that can be used for evaluating XP values and practices. The proposed XP evaluation framework in this study is XP focused and evaluates the XP project, product and practices. The XP evaluation framework is a collection of some new and validated metrics used for evaluating XP projects, XP practices, XP products and some additional factors concerned with XP. The evaluation framework for extreme programming is basically based on the assessment and evaluation of various project characteristics, extreme programming characteristics, product characteristics and other additional characteristics. The metrics used for assessments and evaluations of XP are designed to be simple, precise, understandable, economical, timely, consistent, accountable, unambiguous, suitable and reliable.